(untitled) (ENTHYMEMA, 2014)
The article deals with one storyline of the novel Anna Karenina that stands as the key for the re-search into the significance of Anglomania in the novel. The 1850-1870s in Russian culture is the time of a most intensive formation of the image of the UK as a highly complex combination of real and mythological elements. The novel Anna Karenina, which Tolstoy himself called the novel about modern life, sets forth the fashion for everything ‘English’ in Russian high society in the 1870s with almost documentary precision. The episode the article deals with is Anna Karenina’s reading of an English novel. The article looks at different theories of the origin of the novel and suggests a particular novel as the source for the English novel in Anna Karenina. Article argues that the knowledge of the particular English novel contributes not only to the re-search of Anglomania in Anna Karenina and other Tolstoy’s works but also gives a significant in-sight into the study of the characters in the novel.